2011
DOI: 10.1631/jzus.b1000315
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in aqueous extract of Myristica fragrans (Houtt.) suppress mitosis and cyclophosphamide-induced chromosomal aberrations in Allium cepa L. cells

Abstract: Abstract:In this study, freeze-dried water extract from the leaves of Myristica fragrans (Houtt.) was tested for mutagenic and antimutagenic potentials using the Allium cepa assay. Freeze-dried water extract alone and its combination with cyclophosphamide (CP) (50 mg/kg) were separately dissolved in tap water at 500, 1000, 2000, and 4000 mg/kg. Onions (A. cepa) were suspended in the solutions and controls for 48 h in the dark. Root tips were prepared for microscopic evaluation. 2,2-Diphenyl-1-picrylhydrazyl (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
20
0
2
Order By: Relevance
“…A significant (p<0.01 and <0.001) increase in reduced glutathione (GSH, the vital biological defence molecule against oxidative damage) in liver was reported in this study, in comparison to radiation alone group at day 1, 3, 7, 15 and 30 following irradiation. Some of the recent works (Akinboro et al, 2011;Piaru et al, 2012) further supported the antioxidant property of nutmeg.…”
Section: Myristica Fragransmentioning
confidence: 86%
“…A significant (p<0.01 and <0.001) increase in reduced glutathione (GSH, the vital biological defence molecule against oxidative damage) in liver was reported in this study, in comparison to radiation alone group at day 1, 3, 7, 15 and 30 following irradiation. Some of the recent works (Akinboro et al, 2011;Piaru et al, 2012) further supported the antioxidant property of nutmeg.…”
Section: Myristica Fragransmentioning
confidence: 86%
“…The flavonoids in EE may also be associated with these adverse effects on the cells. On the other hand, in AE the reduction in MI seems to have been caused by synergism of flavonoids and/or saponins, as observed in Myristica fragrans (Akinboro et al, 2011). Studies of cytotoxicity and inhibition of topoisomerase II have been previously reported for diterpenes, 1 Negative control.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are compounds that can inhibit the rate of oxidation or neutralize free radicals. All of these radicals have in common that have one or more unpaired electrons and potentially cause damage to living cells [10]. These unpaired electrons cause free radicals to be highly reactive compounds to the cells of the body by binding to electrons of cell molecules.…”
Section: Introductionmentioning
confidence: 99%